A typology of shī ʿī discourses and possibilities of democracy - Ghobadzadeh, Naser (Critical research on religion, 2023)
This article presents a typology of the major religio-political discourses in the Shī ʿī world, namely Shī ʿa orthodoxy, governmental Shī ʿism, and reformist Shī ʿism. We compare the political stance of the former discourse, which has received the least amount of attention in academic circles, with the other two well-researched discourses. The typology offered in this article will be helpful not only in providing a comprehensive picture of Shī ʿī politico-religious discourses, but also in providing a useful framework for further comparative analyses. We investigate the political theology and history of these discourses, as well as their capacity to accommodate popular sovereignty. We argue that while both orthodox and reformist Shī ʿī discourses embrace popular sovereignty, the linchpin of governmental Shī ʿism is divine sovereignty, which cannot be reconciled with popular sovereignty.